Alkaline-Encrusted Pyelitis Causing Renal Failure in a Transplant Kidney: Treatment with Percutaneous Nephrolithotomy and Urinary Acidification - Johnson, Michael (J Endourol Case Rep, 2020)
Background: Alkaline-encrusted pyelitis (AEP) is rare and most often stems from a triad of immunodeficiency, urogenital tract trauma, and alkaline urinary infection. Corynebacterium Group D2 is the most common organism. It results in encrusting calcifications that adhere to most of the urothelial lining of the pelvicaliceal system and ureter. Left unchecked, or unrecognized, the disease process can progress to renal compromise. Studies suggest that management is based on elimination of the bacterium, acidification of the urine, and elimination of calcified plaques and encrustations. Herein, we report a case of a 56-year-old woman who developed AEP in her second transplanted kidney, and detail the diagnosis and treatment of the uncommon, yet potentially devastating, disease. Case Presentation: A 56-year-old woman with a history of lupus, end-stage renal disease, who was on her second renal transplant presented with symptoms of urinary tract infection. Urine was consistently alkaline with cultures repeatedly growing urease-splitting Corynebacterium. Subsequent imaging showed large obstructing ureteral and renal stones concerning for AEP. She was treated with transplant kidney percutaneous nephrolithotomy, culture-specific antibiotics, and urinary acidification. Conclusion: Clinical presentation, urinalysis, culture, and renal imaging, often with CT, are the mainstays for diagnosing AEP. If not addressed, AEP can advance to renal failure. Management often includes a multimodal approach involving treatment and prevention of the underlying infection, urinary acidification, and percutaneous or endoscopic removal of obstructing and large burden stones and encrustation.